FACILE SYNTHESIS OF ACTIVATED CARBON/ALGINATE/CHITOSAN COMPOSITE BEADS AS RHEMAZOLE BRILLIANT BLUE R ADSORBENT - Hermanto, Dhony; Prihatini, Putri Jauhar; Apriani, Niza Yusnita; Kurniawati, Lely; Murniati, Murniati; Hamdiani, Saprini; Ismillayli, Nurul; Kamali, Siti Raudhatul (Indonesian Physical Review, 2024)
Developing composite beads composed of chitosan, alginate, and activated carbon for dye removal is essential due to their improved adsorption capabilities and environmental benefits. By utilizing natural resources efficiently for an effective dye removal process, this study developed an activated carbon/alginate/chitosan composite bead as Rhemazole Brilliant Blue R (RBBR) adsorbent. The surface shape of composites exhibits more protrusions, grooves, and asymmetric pores than activated carbon, which could improve dye adsorption capability. FTIR analysis verified that functional groups such as OH, NH, protonated amine, and carboxylate from the constituent polymers were enriched in the activated carbon/alginate/chitosan composite. These groups also function as active sites for adsorbents. It was aligned with the composite beads' Freundlich isotherm model, which shows that heterogeneous or many active sites contribute to adsorption and provide multilayer adsorption. The kinetic model of pseudo-second order fits well with the adsorption process, indicating that chemisorption is the rate-limiting step in RBBR adsorption. The optimum adsorption conditions were at pH 1, with an adsorbent dose of 0.08 g, RBBR dye concentration of 125 mg/L, and a contact time of 60 min. The composite beads also exhibit stability in acidic and basic solutions, with the effectiveness of being reused up to four times, providing a reusable adsorbent with versatility in various water treatment conditions. Hence, synthesizing activated carbon/alginate/chitosan composite beads presents a promising solution for sustainable wastewater treatment based on biodegradable and eco-friendly composite. Â